2021
DOI: 10.3390/fermentation7040281
|View full text |Cite
|
Sign up to set email alerts
|

Concentrated Buffalo Whey as Substrate for Probiotic Cultures and as Source of Bioactive Ingredients: A Local Circular Economy Approach towards Reuse of Wastewaters

Abstract: Waste reduction and reuse is a crucial target of current research efforts. In this respect, the present study was focused on providing an example of local investment in a simple process configuration that converts whey into value-added compounds and allows recovery of a clean water stream. In particular, buffalo milk whey obtained during mozzarella manufacturing was ultrafiltered in-house on spiral membrane modules (20 kDa), and the two obtained fractions, namely the retentate and the permeate, provided by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
(34 reference statements)
0
7
0
Order By: Relevance
“…To overcome this issue, various technological approaches have been employed to transform and exploit whey components [3]. In fact, by implementing innovative downstream and biotechnological processes, using membranes, rather than being viewed as a waste product whey may be considered a resource to obtain high added-value products [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. Several methods, such as UF, NF, and ion exchange chromatography, have been used to concentrate and separate proteins and lactose from other components present in second cheese whey.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To overcome this issue, various technological approaches have been employed to transform and exploit whey components [3]. In fact, by implementing innovative downstream and biotechnological processes, using membranes, rather than being viewed as a waste product whey may be considered a resource to obtain high added-value products [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. Several methods, such as UF, NF, and ion exchange chromatography, have been used to concentrate and separate proteins and lactose from other components present in second cheese whey.…”
Section: Discussionmentioning
confidence: 99%
“…SCW, R100, R10, and RNF were also used as a main substrate for probiotic cultures. In fact, thanks to the carbon sources content (lactose, glucose, galactose) in addition to proteins (as reported in Table 1), all are potentially complete substrates for the cultivation of different microorganisms [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] and for the production of value-added chemicals (e.g., succinic acid, lactic acid), antimicrobial peptides, besides the biomass itself [27][28][29]. In the first trial reported in Figure 2, three different Lactobacillus strains were grown on an SCW-based medium, showing that after 17 h, a comparable viability for L. rhamnosus IMC501and L. brevis SP-48 was obtained whereas a far lower concentration of viable cells was found for L. fermentum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…41 The use of membranes not only reduces costs by enabling water reuse and recovery during processing but also assists in compliance with environmental regulations. 42 The streams of demineralized water from whey permeate can be used for primary rinsing in clean-in-place (CIP) cleaning processes, as well as for domestic use in toilets or truck washing in industries. However, for industrial use, specific parameters must be followed to ensure portability and avoid any microbiological risks.…”
Section: Fractionation Of Whey In the Food Industrymentioning
confidence: 99%
“…The use of membranes not only reduces costs by enabling water reuse and recovery during processing but also assists in compliance with environmental regulations 42 …”
Section: Fractionation Of Whey In the Food Industrymentioning
confidence: 99%